2008
DOI: 10.1097/aud.0b013e3181775dde
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Pathways of Vibratory Stimulation as Measured by Subjective Thresholds and Distortion-Product Otoacoustic Emissions

Abstract: To clarify the contribution of the skull contents to the transmission of bone vibratory stimuli, and to examine the characteristics of such stimuli, we compared auditory thresholds and distortion-product otoacoustic emission (DPOAE) levels with a bone vibrator placed on various sites of the head, including the eye. The best audiometric thresholds and the highest DPOAE levels were obtained with the vibrator placed on the mastoid of the measuring side, or on the "ultrasound-window" of the temple. The audiometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 24 publications
2
46
1
2
Order By: Relevance
“…It has been shown that direct stimulation of the soft tissues (i.e., eye or neck) stimulates the cochlea and causes a hearing sensation (11,24,25). In the current measurements, the gain for both the cochlear promontory vibration and intracranial pressure tended to be below 0 dB for stimulation to the eye and neck, relative to stimulation to the mastoid.…”
Section: E388contrasting
confidence: 49%
“…It has been shown that direct stimulation of the soft tissues (i.e., eye or neck) stimulates the cochlea and causes a hearing sensation (11,24,25). In the current measurements, the gain for both the cochlear promontory vibration and intracranial pressure tended to be below 0 dB for stimulation to the eye and neck, relative to stimulation to the mastoid.…”
Section: E388contrasting
confidence: 49%
“…This notion is based on the ability to cancel a BC tone by an AC tone (Stenfelt, 2007;von Békésy, 1932), the ability to generate distortion-product otoacoustic emissions using BC stimulation (Purcell et al, 1998;Watanabe et al, 2008), and the similarity of BM vibration pattern with AC and BC excitation (Stenfelt et al, 2003a). However, the way the sound is transmitted from the excitation position, often at the mastoid or forehead of the skull, to the inner ear and causing the BM vibration is not clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Even though such measurements have been taken for many decades, the exact routes of how the sound reaches the cochlea by BC are still unclear. Pathways of sound through osseous parts of the head have been well documented [Von Bekesy, 1932;Barany, 1938;Wever and Lawrence, 1954;Tonndorf, 1966;Stenfelt, 2005], but recent work Freeman et al, 2000;Sohmer and Freeman, 2004;Watanabe et al, 2008] has revealed that non-osseous head contents such as the cerebrospinal fluid (CSF) also contribute to the sound transmission in BC. Very little is known about the frequency-specific contribution of these different pathways to the hearing sensation evoked by classical measurements of clinical BC.…”
Section: Introductionmentioning
confidence: 99%